2017
DOI: 10.5125/jkaoms.2017.43.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of idiopathic bone cavity: case series of consecutive 27 patients

Abstract: ObjectivesIdiopathic bone cavity (IBC) is an uncommon intra-osseous cavity of unknown etiology. Clinical features of IBC are not well known and treatment modalities of IBC are controversial. The purpose of this study was to investigate the clinical characteristics of 27 IBC patients who underwent surgical exploration.Materials and MethodsA total of 27 consecutive patients who underwent surgery due to a jaw bone cavity from April 2006 to February 2016 were included in this study. Nine male and 18 female patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
51
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(57 citation statements)
references
References 17 publications
5
51
0
1
Order By: Relevance
“…The surgical approach is still considered a safe procedure for the diagnosis and treatment of IBC 18 , 24 . Surgery must be performed for symptomatic cases whenever boundary changes, or size and cortical expansion occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical approach is still considered a safe procedure for the diagnosis and treatment of IBC 18 , 24 . Surgery must be performed for symptomatic cases whenever boundary changes, or size and cortical expansion occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The classic radiographic aspect of IBC is that of a well-defined, unilocular, lucent image whose edges reach in between the roots in a wavy pattern 1,3,4 . However, in this case report, the image was lucent, multilocular, circumscribed, well-defined with cortical expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to connect clinical history, physical examination, and imaging tests, besides surgical exploration for a clearer sight. In some cases, these radio-and tomographic aspects may lead to diagnostic hypothesis of odontogenic tumor, more aggressive diseases with high probability of recurrence 2,4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence of TBC is assumed to be extremely rare, (26) a recent study has reported the recurrence rate of TBC in facial bone to be about 20%. (56) On recurrence, a marked increase in the size with multilocular appearance. (57) If present, recurrence usually occur within three months after surgery.…”
Section: Discussionmentioning
confidence: 99%